1981
DOI: 10.1029/gl008i004p00345
|View full text |Cite
|
Sign up to set email alerts
|

The origin of particulate organic carbon in the marine atmosphere as indicated by its stable carbon isotopic composition

Abstract: Organic carbon concentration and isotopic composition were determined in samples of atmospheric particulate matter collected in 1979 at remote marine locations (Enewetak atoll, Sargasso Sea) during the SEAREX (Sea‐Air Exchange) program field experiments. Atmospheric Particulate Organic Carbon (POC) concentrations were found to be in the range of 0.3 to 1.2µg.m−3, in agreement with previous literature data. The major mass of POC was found on the smallest particles (r<0.5µm). The 13C/12C of the small particles i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(112 citation statements)
references
References 11 publications
5
105
1
Order By: Relevance
“…The δ 13 C values are relatively small, ranging from −24.7 ‰ to −29.7 ‰ with an average of −26.5 ‰. These low values suggest that the aerosol carbon may be derived from organic matter of terrestrial plant origin (Chesselet et al, 1981;Cachier et al, 1986;Kawamura et al, 2004;Narukawa et al, 2008). Because the surface waters in the Canadian Shelf of the Beaufort Sea are significantly influenced by the freshwater inflow from the Mackenzie River (Carmack et al, 2004), terrestrial organic materials are supplied to the surface ocean and then emitted to the air by bubble bursting processes associated with wind action.…”
Section: Samples and Methodsmentioning
confidence: 96%
“…The δ 13 C values are relatively small, ranging from −24.7 ‰ to −29.7 ‰ with an average of −26.5 ‰. These low values suggest that the aerosol carbon may be derived from organic matter of terrestrial plant origin (Chesselet et al, 1981;Cachier et al, 1986;Kawamura et al, 2004;Narukawa et al, 2008). Because the surface waters in the Canadian Shelf of the Beaufort Sea are significantly influenced by the freshwater inflow from the Mackenzie River (Carmack et al, 2004), terrestrial organic materials are supplied to the surface ocean and then emitted to the air by bubble bursting processes associated with wind action.…”
Section: Samples and Methodsmentioning
confidence: 96%
“…(1) the influence of sub-micron aeolian particles in smaller POM with lighter carbon signatures (d 13 C 5 226.5% to 226.7%; Chesselet et al 1981); (2) changes in relative terrestrial OM contribution (Hernes and Benner 2002); or (3) fundamental differences in stable isotopic fractionation between small vs. larger marine unicellular organisms, such that POM size fractions may reflect differences in primary producer community composition (i.e., eukaryotic vs. prokaryotic; Close et al 2011;A. Pearson pers.…”
Section: Resultsmentioning
confidence: 99%
“…Indications are that the 0.1-0.7 mm size fraction could account for as much as 40-50% of suspended POC Altabet, 1990). Studies have shown that carbon associated with aerosol particles are largely in this size fraction (Hoffman and Duce, 1977;Chesselet et al, 1981) and that the d 13 C of aerosols (À26.5 to À26.7%) over the Pacific and Atlantic Oceans indicate a terrigenous origin (Chesselet et al, 1981). A simple mixing model, in which all particles greater than 0.7-0.8 mm are considered marine with a d 13 C of À22%, and all smaller particles are considered terrestrial with a d 13 C of À27%, results in total particulate d 13 C values more depleted than À24%.…”
Section: Sources Of Pommentioning
confidence: 99%